Analyzing Factors Affecting Overall Customer Satisfaction Using Hotel Ratings and Reviews With BERTopic and Three-Factor Theory - Jun Li; Byunghyun Lee; Jaekyeong Kim (SAGE Open)
This research was conducted to aid hotels in identifying and enhancing the hotel selection attributes that customers deem important for maintaining revenue and competitive advantage. Departing from conventional survey methods, we utilized BERTopic on the extensive review data from TripAdvisor to extract crucial hotel selection attributes. Through RIPA and PRCA analyses across various hotel star ratings, we sought insights into customer perceptions. The findings unveiled eight hotel selection attributes deemed significant by customers, revealing no differences in implicitly derived importance, satisfaction performance and overall customer satisfaction for staff, trip type, and resort fees across hotel star ratings. However, variations were evident in other hotel selection attributes. Thus, in contrast to prior studies, this research employed big data techniques like BERTopic for topic extraction and utilized PRCA additionally to compensate for the limitations of RIPA, identifying differences among attributes included in the same quadrant.